THE EFFECT OF OVERCONFIDENCE BIAS, HERDING, AND ACCOUNTING LITERACY ON INVESTING DECISION MAKING WITH ESCALATION OF COMMITMENT AS AN INTERVENING VARIABLE (EMPIRICAL STUDY ON GENERATION Z INVESTORS IN MEDAN CITY) - Thezar Fiqih Hidayat Hasibuan; Minda Muliana Sebayang; Sari Nuzullina Rahmadhani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of behavioral factors (Overconfidence Bias and Herding) and Accounting Literacy on Investing Decision Making among Generation Z investors in Medan City, with Escalation of Commitment as an intervening variable. Generation Z is known as a new group of aggressive investors but is vulnerable to psychological bias and the influence of social trends ( fear of missing out ). The research method used is quantitative by distributing questionnaires to Gen Z stock investors domiciled in Medan City. Data were analyzed using Structural Equation Modeling (SEM). This article discusses the conceptual framework and hypotheses built based on Behavioral Finance Theory and Prospect Theory .